Women’s Leadership via Digital Technology and Entrepreneurship in business and society - Karyotaki , Maria; Bakola, Lizeta; Drigas, Athanasios; Skianis, Charalabos (Technium Social Sciences Journal, 2022)
Gender equality and digital development are inextricably linked. On the other hand digital skills are in increased demand due to the digital skill gap expanding. Most of the tech nation’s reports have shown that men still outweigh women by 3 to 1. This study aims to expound the relationship between digital technology and women’s leadership in business and society and try to clarify the reasons that women fall short of the demands of the digital sector as it is increasingly growing.